Respostas
respondido por:
53
A1= 1 A2=3+x A3=17-4x
A média de A1+A3= A2
Logo, temos:
1+17-4x/2=3+x
1+17-4x=6+2x
12=6x
x=12/6
x=2
A média de A1+A3= A2
Logo, temos:
1+17-4x/2=3+x
1+17-4x=6+2x
12=6x
x=12/6
x=2
respondido por:
22
a média de a1 e a3 é igual a2
a1+ a3 / 2 = a2
1 + 17-4x = 3 + x
18 - 4x = 2(3 +x)
18 - 4x = 6 + 2x
18 - 6 = 2x + 4x
12 = 6x
x =12 / 6
x =2
a1+ a3 / 2 = a2
1 + 17-4x = 3 + x
18 - 4x = 2(3 +x)
18 - 4x = 6 + 2x
18 - 6 = 2x + 4x
12 = 6x
x =12 / 6
x =2
Perguntas similares
7 anos atrás
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás